Formation of Nanocomposites by Oxidizing Annealing of SiO(x) and SiO(x)<Er,F> Films: Ellipsometry and FTIR Analysis - Sopinskyy, Mykola V (Nanoscale Res Lett, 2015)
The structural-phase transformations induced by air annealing of SiO(x) and SiO(x) < Er,F > films were studied by the combined use of infrared spectroscopy and ellipsometry. The films were prepared using vacuum evaporation of SiO powder and co-evaporation of SiO and ErF(3) powders. The annealing took place at moderate temperatures (750 and 1000 °C). It was found that the micro- and macrostructure of the annealed films is similar to the structure of the Si–SiO(x) nanocomposites obtained by annealing SiO(x) in vacuum or inert atmosphere and subjected to post-annealing in oxidizing atmosphere. This proves that the phase separation in the non-stoichiometric SiO(x) films proceeds much faster than their oxidation. The results of the work point at a possibility to simplify the annealing technology by replacing the two-step annealing with one-step in the oxygen-containing environment while maintaining the positive effects. The differences in the structure of the nanocomposites obtained by annealing the SiO(x) and SiO(x) < Er,F > films are explained by the action of Er centers as the promoters for SiO(x) disproportionation, as well as the enhanced action of F on the processes of disorder-to-order transition and crystallization in amorphous silicon.